(3OjhGf GdMGOQIs - (3bWHI Hf ChS Hf eMUf Hf LQhd GdeGRfj GdaRGQj GdZWaGfqj, jdbH HGdMGOQI (B((3GdVNe(B) (3Ch GdMhjOQI , J (B( (3O J (B)s
(3ChdgG (B:s
(3bGd GdjRjOj(B: (3bQCJ Ydi YHOGdQMef Hf YHOGddg Hf bQjH Hf CNj GdCUeYj, bGd GdMGOQI, hGSeI hEfeG oSej GdMGOQI dbhd RHGf Hf SjGQ GdaQGRj dg s
(3BNQgG (B:s
(3GdebHdjf fMhQ Njdge LO GdQeGM hZHjI GdfHd hEf TQ GdZHjG ZHjI GdfHd, hEf TQ GdfSGA GdMejQGA GdeMjGV, hGdShjOGA GdeeQGV s
(3GdfSNI HgG MhGTs
(3YdjgG faS GdJbjjOGJ hGdTQhM GdehLhOI HGdfSNI GdChdis
(3aj CKfGFgG SbW fHg Ydjg Ydi MhGTjgGs
(3fSNI QGHYIs
(3QhGjI CHj YHOGddg eMeO Hf GdYHGS GdjRjOj s
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs